DATA MINING ESTIMATE TOURISM INCOME IN TOMOHON CITY USING MULTIPLE LINEAR REGRESSION ALGORITHMS - Karamoy, Beauty Leony; Rantung, Vivi Peggie; Kumajas, Sondy; Ratumbuisang, Yosua Fitsgerald (Informatika, Universitas Jenderal Soedirman, 2024)
This study aims to estimate the revenue of tourist destinations in Tomohon City using the multiple linear regression algorithm. The problem addressed is how to determine revenue estimates from various tourist spots categorized into nature tourism and cultural experiences. The research method employed is quantitative, using a multiple linear regression approach. Data were collected through interviews with tourist destination owners regarding ticket prices and visitor numbers, and then analyzed using Microsoft Excel. The results show that the independent variables, consisting of ticket prices (X1) and the number of visitors (X2), significantly affect the dependent variable, which is monthly revenue (Y). The regression equation model obtained is Y = -5594 + 250X1 + 2.26X2. Using this model, the next month's revenue prediction for each tourist destination in Tomohon City can be determined, demonstrating that the multiple linear regression approach is effective for estimating tourism revenue.